TECHNIQUES OF URBAN RENEWAL FOR THE URBAN HERITAGE -The case of M’zab Valley - - زناتي, جلول (Journal of Planner and Development, 2012)
Considerations the architectural heritage, fabric and functional relations impediment to progress and development, has led to the application of regulatory policies that have led to many problems, which are still far are still visible, and impose a strong presence during the dealing with architectural heritage, in terms of plans and strategies to preserve the cultural heritage and renewal. The series of actions and changes that have occurred in the city, has been applied without taking into account the social and cultural distinctive, and led to serious structural changes in the urban fabric and organic space.     Faced with this exceptional situation, there have been many calls to the importance of preserving the architectural heritage material and moral entity at the same time, and to refrain from considering them as areas of archaeological historical, but also as spaces of urban areas of activity and exchange of cultural and economic.